Pengembangan Instrumen Pre-Lab Berbasis Kecakapan Laboratorium Dasar - Junaidi, Eka; Anwar, Yunita Arian Sani; Muti’ah, Muti’ah; Burhanuddin, Burhanuddin; Al Idrus, Syarifa Wahidah; Ramadhani, Siti Rumaisah (FKIP University of Mataram, 2024)
Pre-lab activities have not been a serious concern, especially in the development of instruments. Until now, pre-lab activities have only provided tests based on work procedures or concepts described in the practicum instructions. Instruments capable of measuring various aspects of basic laboratory skills have not been widely developed. This study aims to develop a pre-laboratory instrument based on basic laboratory skills. Five categories of basic skills were identified: procedural, manipulative, observation, interpretation, and conclusion skills. A total of 20 items, representing various aspects of the identified skills, were developed and deemed feasible through expert agreement. Testing the instrument on 45 respondents revealed that 15 questions met the criteria for validity (p<0.05) and demonstrated good reliability.